Patient with Martin-Bell syndrome and premenstrual syndrome, tendency for obesity from puberty - Grażyna Jarząbek-Bielecka; Małgorzata Mizgier; Katarzyna Plagens-Rotman; Piotr Merks; Katarzyna Wróblewska-Seniuk; Witold Kędzia; Magdalena Pisarska-Krawczyk (IMR Press, 2022)
Background: Fragile X syndrome (FRA X) is the most common cause of inherited moderate intellectual disability. The cause of FRA X syndrome is a dynamic mutation in the FMR1 gene (located on the X sex chromosome-long arm, position 27.3, between base pairs 147 911 951 and 147 951 125). Case(s): A patient born in 1993 along with her mother was referred to the Department of Developmental Age Gynaecology and Gynaecological Sexology of the Obstetrical Clinical Hospital at the Poznań University of Medical Sciences (Poland) because of existing recurrent menstrual cycle disorders and recurrent genital inflammation. From her history since childhood, this patient had fluctuating body weight with a tendency for overweight and obesity. Contact with the patient was difficult, she was reluctant to answer questions during the medical interview. There is a family history of intellectual disability. The patient required continuous gynaecological and psychiatric care, diet therapy, physical activity was recommended, which had a beneficial effect on the patient's somatic and mental health. Conclusions: The diagnosis of fragile X syndrome involved not only the patient but also her family in a very broad interdisciplinary approach, also in terms of genetic counselling. Additional problems with cycle disorders, genital inflammation and weight disorders mean that the patient will still require gynaecological and psychiatric care, diet therapy, and physical activity has been recommended, which has a beneficial effect on the patient's somatic and mental health.